In-vitro and in-vivo validation of ethnopharmacological uses of methanol extract of Isodon rugosus Wall. ex Benth. (Lamiaceae) - Janbaz, Khalid Hussain; Arif, Javeria; Saqib, Fatima; Imran, Imran; Ashraf, Muhammad; Zia-Ul-Haq, Muhammad; Jaafar, Hawa Z. E.; De Feo, Vincenzo (BioMed Central, 2014)
Background: Isodon rugosus is used in folk Pakistan traditional practices to cure ailments related to gastrointestinal, respiratory and cardiovascular problems. Present study was undertaken to validate these folkloric uses. Methods: A crude methanol extract of the aerial parts of Isodon rugosus (Ir.Cr.) was used for both in vitro and in vivo experiments. The plant extract was tested on isolated rabbit jejunum preparations for possible presence of spasmolytic activity. Moreover, isolated rabbit tracheal and aorta preparations were used to ascertain the relaxant effects of the extract. Acetylcholinesterase and butyrylcholinesterase inhibitory activities of Ir.Cr were also determined as well as its antioxidant activity. The in vivo antiemetic activity of the extract was evaluated by using the chick emesis model, while the analgesic and antipyretic activities were conducted on albino mice. Results: The application of the crude extract of I. rugosus to isolated rabbit jejunum preparations exhibited relaxant effect (0.01-0.3 mg/ml). The Ir.Cr also relaxed K+(80 m M)-induced spastic contractions in isolated rabbit jejunum preparations and shifted the Ca+2 concentration response curves towards right (0.01-0.3 mg/ml). Similarly, the extract, when applied to the isolated rabbit tracheal preparations relaxed the carbachol (1 μM)- as well as K+ (80 mM)-induced contractions in a concentration range of 0.01-1.0 mg/ml. Moreover, it also relaxed (0.01-3.0 mg/ml) the phenylephrine (1 μM)- and K+ (80 mM)-induced contractions in isolated rabbit aorta preparations. The Ir.Cr (80 mg/kg) demonstrated antipyretic activity on pyrogen-induced pyrexia in rabbits as compared to aspirin as standard drug. The Ir.Cr also exhibited anti-oxidant as well as inhibitory effect on acetyl- and butyryl- cholinesterase and lipoxygenase (0.5 mg/ml). Conclusions: The observed relaxant effect on isolated rabbit jejunum, trachea and aorta preparations caused by Ir.Cr is possibly to be mediated through Ca+2 channel blockade and therefore may provided scientific basis to validate the folkloric uses of the plant in the management of gastrointestinal, respiratory and cardiovascular ailments. The observed antioxidant activity as well as the lipoxygenase inhibitory activity may validate its traditional use in pain and inflammations.